Nephelometry and Turbidimetry: Methods to Quantify Albumin and Immunoglobulins Concentrations in Clinical Neurochemistry - Lewczuk, Piotr (Neuromethods, 2021)
CSF concentrations of albumin and immunoglobulins (IgG, IgA, and IgM) are contemporary analyzed by fully automated, particle-enhanced turbidimetry or nephelometry. Turbidimetry measures decrease of the intensity of light passing through a solution (a CSF sample) due to its scattering on the particles suspended in this sample. Nephelometry applies a similar principle, but with a light detector placed at an angel to the source. This allows measurement of the intensity of the light reflected on the particles suspended in a sample. Diagnostically relevant are concentrations of albumin, IgG, IgA, and IgM. To normalize their CSF concentrations for the concentrations in the blood, the results are expressed as CSF/serum concentrations quotients (i.e., QAlb). Since albumin is generated exclusively in the liver, it diffuses passively into the CSF through the blood–CSF barrier, and it is not metabolized by the brain, QAlb is the biomarker of choice for the blood–CSF barrier function. In contrast, under pathologic conditions, like neuroinflammations, immunoglobulins may be synthesized intrathecally. Two phenomena need be considered to correctly interpret immunoglobulins concentrations in the CSF: (a) passive diffusion through the blood–CSF barrier and (b) possible release from intrathecal lymphocytes. Hence, “references” for the CSF immunoglobulins quotients exist only dependent on the blood–CSF barrier staus (i.e., QAlb). Hyperbolic functions proposed by H. Reiber in 1990s describe the correlation between QAlb and QIg, enabling correct interpretation of the immunoglobulins concentrations found in the CSF. Furthermore, distinctive features of the intrathecal immune response, characteristic for the CSF, need to be taken into consideration to properly interpret albumin/immunoglobulins patters.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Blood–CSF barrier function; Nephelometry; Neuroinflammation; Reibergram; Turbidimetry